Transesophageal Speckle-Tracking Echocardiography Improves Right Ventricular Systolic Function Assessment in the Perioperative Setting - Markin, Nicholas W.; Chamsi-Pasha, Mohammed; Luo, Jiangtao; Thomas, Walker R.; Brakke, Tara R.; Porter, Thomas R.; Shillcutt, Sasha K. (Journal of the American Society of Echocardiography, 2017)
Perioperative evaluation of right ventricular (RV) systolic function is important to follow intraoperative changes, but it is often not possible to assess with transthoracic echocardiographic (TTE) imaging, because of surgical field constraints. Echocardiographic RV quantification is most commonly performed using tricuspid annular plane systolic excursion (TAPSE), but it is not clear whether this method works with transesophageal echocardiographic (TEE) imaging. This study was performed to evaluate the relationship between TTE and TEE TAPSE distances measured with M-mode imaging and in comparison with speckle-tracking TTE and TEE measurements. Prospective observational TTE and TEE imaging was performed during elective cardiac surgical procedures in 100 subjects. Speckle-tracking echocardiographic TAPSE distances were determined and compared with the TTE M-mode TAPSE standard. Both an experienced and an inexperienced user of the speckle-tracking echocardiographic software evaluated the images, to enable interobserver assessment in 84 subjects. The comparison between TTE M-mode TAPSE and TEE M-mode TAPSE demonstrated significant variability, with a Spearman correlation of 0.5 and a mean variance in measurement of 6.5 mm. There was equivalence within data pairs and correlations between TTE M-mode TAPSE and both speckle-tracking TTE and speckle-tracking TEE TAPSE, with Spearman correlations of 0.65 and 0.65, respectively. The average variance in measurement was 0.6 mm for speckle-tracking TTE TAPSE and 1.5 mm for speckle-tracking TEE TAPSE. Using TTE M-mode TAPSE as a control, TEE M-mode TAPSE results are not accurate and should not be used clinically to evaluate RV systolic function. The relationship between speckle-tracking echocardiographic TAPSE and TTE M-mode TAPSE suggests that in the perioperative setting, speckle-tracking TEE TAPSE might be used to quantitatively evaluate RV systolic function in the absence of TTE imaging. •TTE M-mode TAPSE and TEE M-mode TAPSE do not agree, and TEE M-mode TAPSE should not be used to quantify RV systolic function.•Speckle-tracking echocardiography allows accurate TAPSE measurements for TTE and TEE imaging compared with TTE M-mode TAPSE.•Speckle-tracking TEE TAPSE could be used to quantify RV systolic function in the perioperative setting when standard TTE methods are not possible.